1999
DOI: 10.1016/s0169-4332(98)00553-4
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the optimal imaging parameters for frequency modulation atomic force microscopy

Abstract: True atomic resolution of conductors and insulators is now routinely obtained in vacuum by frequency modulation atomic Ž force microscopy. So far, the imaging parameters i.e., eigenfrequency, stiffness and oscillation amplitude of the cantilever, . frequency shift which result in optimal spatial resolution for a given cantilever and sample have been found empirically. Here, we calculate the optimal set of parameters from first principles as a function of the tip-sample system. The result shows that the either … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(153 citation statements)
references
References 17 publications
4
147
0
2
Order By: Relevance
“…The link between the tip-surface interaction and an NC-SFM simulated image is a model of the oscillations of the cantilever under the influence of the tip-surface interaction. Detailed analyses of the tip oscillations and ways to model them are given by Giessibl (1995Giessibl ( , 1997; Aimé et al (1999); Giessibl et al (1999); Sasaki and Tsukada (1999); Dü rig (2000); Schwarz, Hö lscher, and Wiesendanger (2000); García and Pé rez (2002); Morita et al (2002). However, a simple model can be derived under some basic assumptions.…”
Section: E Modeling Oscillationsmentioning
confidence: 99%
“…The link between the tip-surface interaction and an NC-SFM simulated image is a model of the oscillations of the cantilever under the influence of the tip-surface interaction. Detailed analyses of the tip oscillations and ways to model them are given by Giessibl (1995Giessibl ( , 1997; Aimé et al (1999); Giessibl et al (1999); Sasaki and Tsukada (1999); Dü rig (2000); Schwarz, Hö lscher, and Wiesendanger (2000); García and Pé rez (2002); Morita et al (2002). However, a simple model can be derived under some basic assumptions.…”
Section: E Modeling Oscillationsmentioning
confidence: 99%
“…These long-range attractive forces are greatly reduced in liquid, making it possible to oscillate the cantilever with small amplitude. The small-amplitude operation is proven to be Frequency [Hz] (c) (b) effective for enhancing the sensitivity to the short-range interaction force, 23 thereby obtaining high spatial resolution. 24 For a reasonable immunity to the electronic circuit noise, the amplitude of the deflection signal should be larger than 100 mV, while the amplitude should be kept lower than a few volts to avoid the harmonic distortions caused by the insufficient slew rate of the OPAMP at high frequencies.…”
Section: B Differential Amplifiermentioning
confidence: 99%
“…The initial values for k and A have been found empirically and a theoretical study has shown that maximum signal-to-noise ratio should be obtained with AϷ0.3-1 nm. 6 For achieving stable oscillation with such small amplitudes, the spring constant k of the CL must be of the order of a few hundred newtons per meter. These findings have motivated the attempt to achieve atomic resolution with quartz tuning forks with a stiffness of a few kilonewtons per meter.…”
mentioning
confidence: 99%